Thermography and Thermometry in Medicine. The Importance and Use of Non-Invasive Methods in the Diagnostics of Certain Diseases - Ostafiychuk, D.I.; Shaiko-Shaikovsky, O.G. (Journal of Thermoelectricity, 2025)
Thermography and thermometry are modern diagnostic methods that are currently increasingly used in medical research due to their sufficient information content and non-invasiveness. The paper examines the possibilities of thermography in modern medical diagnostics, analyzes the literature on thermographic and thermometric research methods, and identifies the main areas of application of the method in medicine. The biophysical aspects of thermography, physiological and physical factors that influence the formation of thermographic and thermometric diagnostics have been identified.